2021
DOI: 10.3390/ijerph18147463
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the Maternal and Child Health Handbook and Other Home-Based Records on Newborn and Child Health: A Systematic Review

Abstract: Home-based records are paper or electronic records retained and used by mothers or caregivers to document the health services received for maternal, newborn, and child health. Little has been studied about the roles of these records on newborn and child health outcomes. Hence, we collated and summarized evidence concerning the roles of home-based records in improving newborn and child health. We conducted a systematic search in several databases: MEDLINE, Web of Science, CINAHL, PsycINFO, PsycARTICLES, Academi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 49 publications
0
8
0
2
Order By: Relevance
“…We believe that the information on congenital malformations is highly accurate because it is based on maternal and child health handbooks. 3 On the other hand, we believe it is important to interview the patient multiple times during the pregnancy. Thus, starting in May 2022, we obtained detailed information on drug use multiple times during the entire pregnancy via phone, email, and a web-based system.…”
Section: Toward Improving the Reliability Of Safety Information On Dr...mentioning
confidence: 99%
“…We believe that the information on congenital malformations is highly accurate because it is based on maternal and child health handbooks. 3 On the other hand, we believe it is important to interview the patient multiple times during the pregnancy. Thus, starting in May 2022, we obtained detailed information on drug use multiple times during the entire pregnancy via phone, email, and a web-based system.…”
Section: Toward Improving the Reliability Of Safety Information On Dr...mentioning
confidence: 99%
“…The World Health Organization (WHO) along with some studies recommended MCH-HB as one form of HBR to improve health service utilization [9][10][11][12]. Furthermore, the MCH-HB functions as a self-learning resource, helps avoid multiple HBRs [13], and supports improvements in CoC [14][15][16]. Therefore, the MCH-HB has drawn greater attention from health ministries and professional organizations across the globe for being an effective tool for promoting a life course approach to healthcare [8].…”
Section: Introductionmentioning
confidence: 99%
“…Its use originated in Japan in 1948 and it is known to be the first integrated home-based record covering the entire spectrum of pregnancy, childbirth, infancy and childcare until 6 years of age 4. The integration may have facilitated the continuum of care5 and might help achieve the Sustainable Development Goal (SDG) 3—ensuring healthy lives and promoting well-being for all at all ages 6. As part of universal healthcare, this handbook is distributed to pregnant women in Japan when they register their pregnancy 7.…”
Section: Introductionmentioning
confidence: 99%
“…Previous systematic reviews have evaluated the impact of home-based records on MNCH and reported improvements in the uptake of antenatal care services, childhood vaccinations and newborn and childcare practices 5 10 11. Studies in Myanmar and Palestine also showed a positive association between using the MCH handbook and receiving high-quality maternal health services 8 12.…”
Section: Introductionmentioning
confidence: 99%